Lateral olivocochlear neurons modulate cochlear responses to noise exposure - Austen A. Sitko; Michelle M. Frank; Gabriel E. Romero; Mackenzie Hunt; Lisa V. Goodrich (Proceedings of the National Academy of Sciences, 2025)
The sense of hearing originates in the cochlea, which detects sounds across dynamic sensory environments. Like other peripheral organs, the cochlea is subjected to environmental insults, including loud, damage-inducing sounds. In response to internal and external stimuli, the central nervous system directly modulates cochlear function through olivocochlear neurons (OCNs), which are located in the brainstem and innervate the cochlear sensory epithelium. One population of OCNs, the lateral olivocochlear (LOC) neurons, target spiral ganglion neurons (SGNs), the primary sensory neurons of the ear. LOCs alter their transmitter expression for days to weeks in response to noise exposure (NE), suggesting that they could tune SGN excitability over long time periods in response to auditory experience. To examine how LOCs affect auditory function after NE, we characterized OCN transcriptional profiles and found transient LOC-specific gene expression changes after NE, including upregulation of multiple neuropeptide-encoding genes. Next, by generating intersectional mouse lines that selectively target LOCs, we chemogenetically ablated LOCs and assayed auditory responses at baseline and after NE. Compared to controls, mice with reduced LOC innervation showed greater NE-induced functional deficits 1 d later and had worse auditory function after a 2-wk recovery period. The number of remaining presynaptic puncta at the SGN synapse with inner hair cells did not differ between control and LOC-ablated animals, suggesting that the primary role of LOCs after NE is likely not to protect but instead to compensate, ensuring that SGN function is enhanced during periods of need.